Green is the New Black: Above Grounders and Below Grounders Seeded to Deconstruct Civilization - Ehret, Matthew (Matt Ehret's Insights, 2025)
In the 2022 Hollywood film How to Blow Up a Pipeline several young, anxiety ridden eco-activists conspire together to literally blow up pipelines in Texas to save civilization.